Circular Economy, Pengelolaan Sampah Organik melalui Budidaya Maggot dan Jamur Tiram di Kecamatan Sambikerep Surabaya - Angela Linggo Satria; Praptini Yulianti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This project aims to manage organic waste in Sambikerep District, Surabaya, through the cultivation of maggots and oyster mushrooms as part of a circular economy concept. The activity is conducted by Master of Management students from Universitas Airlangga in a Creating Shared Value (CSV) program to support the achievement of Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 13 (Climate Action). This program provides economic opportunities for low-income communities, especially housewives, and promotes climate change adaptation and mitigation. The program’s success indicators include the number of participants, participant feedback, and the availability of supporting facilities, all of which were achieved successfully. A Social Return on Investment (SROI) analysis was also conducted to assess the program's impact on stakeholders, including students, local residents, and partners. The program results provide various skills and benefits, such as leadership, communication, and community relations, measured in monetary terms as a proxy for the training and resources provided.